2020
DOI: 10.1111/add.14902
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selective outcome reporting and trial registration practices among addiction clinical trials

Abstract: Background and Aims Selective outcome reporting occurs when trialists pre-specify primary and secondary outcomes during trial planning but alter the definitions in the published report. Here, we investigate selective outcome reporting in published addiction randomized controlled trials (RCTs) and evaluate whether particular funding sources are associated with an increased likelihood of selective outcome reporting. Design We conducted a cross-sectional study of published addiction clinical trials. A PubMed sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…For example, researchers may select which particular study or hypothesis to preregister; they may preregister a study only after running a long series of calibration tests that are not reported; they may preregister multiple studies or versions of the same study, then only report a selection; they may intentionally or unintentionally specify the hypotheses to be tested and analyses to be performed in loose terms, hence buying themselves flexibility in subsequent testing and analyses. Moreover, it is not uncommon for published research that was formally preregistered to deviate in material ways from the preregistration (e.g., using different exclusion criteria or a different statistical model than what was preregistered), without proper disclosure (Claesen et al, 2019; Ofosu & Posner, 2019; Vassar, Roberts, Cooper, Wayant, & Bibens, 2019). There is even a danger that some unscrupulous researcher would “preregister” a study or an analysis after it has been conducted or performed—a form of fraud known as “PARKing” (Preregistering After Results are Known; Yamada, 2018).…”
Section: Is Preregistration Sufficient For Good Science?mentioning
confidence: 99%
“…For example, researchers may select which particular study or hypothesis to preregister; they may preregister a study only after running a long series of calibration tests that are not reported; they may preregister multiple studies or versions of the same study, then only report a selection; they may intentionally or unintentionally specify the hypotheses to be tested and analyses to be performed in loose terms, hence buying themselves flexibility in subsequent testing and analyses. Moreover, it is not uncommon for published research that was formally preregistered to deviate in material ways from the preregistration (e.g., using different exclusion criteria or a different statistical model than what was preregistered), without proper disclosure (Claesen et al, 2019; Ofosu & Posner, 2019; Vassar, Roberts, Cooper, Wayant, & Bibens, 2019). There is even a danger that some unscrupulous researcher would “preregister” a study or an analysis after it has been conducted or performed—a form of fraud known as “PARKing” (Preregistering After Results are Known; Yamada, 2018).…”
Section: Is Preregistration Sufficient For Good Science?mentioning
confidence: 99%
“…2 Vassar et al 3 also found inadequate intervention reporting among randomized control trials (RCTs) investigating alcohol use disorder and evidence of selective outcome reporting bias among those examining addiction. 4 Likely as a result of reports such as those, the National Institute on Drug Abuse issued a statement in 2013 calling for improvement in reproducibility and transparency in research. 5 The importance of sound, quality evidence in addiction research cannot be overstated.…”
mentioning
confidence: 99%
“…The paper by Vassar et al . , along with findings from other academic disciplines , show that we are still a long way from resolving the credibility or reproducibility crisis that exists in many fields of empirical research. Specifically, these studies highlight the limited inroads made by pre‐registration, one of the main tools available to academic journals to improve the quality and integrity of published research.…”
mentioning
confidence: 93%
“…However, if there is little or no oversight of what is actually reported in manuscripts from pre‐registered studies, and many continue to selectively report favorable outcomes (approximately a third of pre‐registered clinical trials, according to Vassar et al . ), then journals are aiding the authors of these manuscripts in deceiving readers into believing that the results presented have greater validity than those from unregistered studies. In this manner, journals that insist on pre‐registration but do little to ensure adherence might be doing more damage to research credibility than those that do not require registration at all.…”
mentioning
confidence: 99%
See 1 more Smart Citation